2013
DOI: 10.1007/s00216-013-7000-4
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography–triple quadrupole tandem mass spectrometry: a powerful tool for the (ultra)trace analysis of multiclass environmental contaminants in fish and fish feed

Abstract: A new method for rapid determination of 73 target organic environmental contaminants including 18 polychlorinated biphenyls, 16 organochlorinated pesticides, 14 brominated flame retardants and 25 polycyclic aromatic hydrocarbons in fish and fish feed using gas chromatography coupled with triple quadrupole tandem mass spectrometry (GC-MS/MS) was developed and validated. GC-MS/MS in electron ionization mode was shown to be a powerful tool for the (ultra)trace analysis of multiclass environmental contaminants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…1; Table 1). Since the first published application of the QuEChERS (quick, easy, cheap, effective, rugged, and safe) method for the analysis of pesticides in produce, this method has gained usefulness in pesticide analysis in feed, 2,[5][6][7]11 biological fluids, and tissue samples. 4,8,10,14 In the current study, a QuEChERS clean-up method followed by GC-MS analysis using a library search for unknowns has been used for the analysis of bovine rumen contents to screen for a variety of toxicants commonly encountered in veterinary toxicology laboratories.…”
Section: Research-article2014mentioning
confidence: 99%
“…1; Table 1). Since the first published application of the QuEChERS (quick, easy, cheap, effective, rugged, and safe) method for the analysis of pesticides in produce, this method has gained usefulness in pesticide analysis in feed, 2,[5][6][7]11 biological fluids, and tissue samples. 4,8,10,14 In the current study, a QuEChERS clean-up method followed by GC-MS analysis using a library search for unknowns has been used for the analysis of bovine rumen contents to screen for a variety of toxicants commonly encountered in veterinary toxicology laboratories.…”
Section: Research-article2014mentioning
confidence: 99%
“…However, there are some limitations in mass spectrometry due to matrix effects (ME), which can be particularly pronounced in complex matrices such as fish, where the analyte elutes together with other molecules, which without sufficient purification can lead to amplification or suppression of the analyte signal and can quantitatively alter the results of the analysis. For this reason, isotopically labeled internal standards are very often used to correct matrix effects [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…However, the determination of COPs using triple quadrupole gas chromatography-mass spectrometry (GS-MS/MS) is still scarce. Most studies have found gas chromatography (GC) coupled with triple quadrupole tandem mass spectrometry (MS/MS) operated in electron ionisation mode (EI) to be an effective tool for (ultra)trace analysis [27]. Triple quadrupole MS/MS helps to establish the relationships between ions in a mass spectrum and identify the ions formed when the other ions in the spectrum undergo fragmentation [28].…”
Section: Introductionmentioning
confidence: 99%